Bouquetins et Pyrénées II - Inventaire des représentations du Paléolithique pyrénéen Offert à Jean Clottes, conservateur général du Patrimoine honoraire - Averbouh, Aline; Feruglio, Valérie; Plassard, Frédéric; Sauvet, Georges (Préhistoires de la Méditerranée, 2022)
Emblematic animal of the Pyrenees, the Ibex has inhabited its two slopes since the most ancient times. By adapting to this environment, a typical Pyrenean form Capra pyrenaica pyrenaica appeared several millennia ago. Consumed during Prehistory, the Ibex became, during the Upper Paleolithic, an unavoidable figure of the prehistoric bestiary. Many of its representations are world-famous: painted Ibex from the Salon Noir (Niaux cave, Ariège) or sculpted on sperm whale teeth (Mas d'Azil cave, Ariège). This second volume of the book "Ibex and Pyrenees" is devoted to these prehistoric figurations and offers a detailed inventory for the French and Spanish Pyrenees that is completely new and richly illustrated. It also presents Palaeolithic sites outside the Pyrenees in which the ibex is well represented. Beyond its iconographic interest, accessible to all audiences, this inventory is intended to become a working tool for researchers and teachers; it has therefore been structured with this objective in mind and is coupled with an evolving online database. It brings together more than a hundred French, Spanish, Portuguese, Italian, Belgian and Australian specialists and, like the first volume, is dedicated to Jean Clottes, a prehistorian from the Ariège region, honorary general curator of Heritage at the Ministry of Culture and an international specialist of decorated caves.